Effects of clipping on the error performance of OFDM in frequency selective fading channels. - Panta, K.R (IEEE Transactions on wireless communications)
Previous studies on the effect of the clipping noise on the error performance of orthogonal frequency-division multiplexing (OFDM) systems in frequency selective fading channels provide pessimistic results. They do not consider the effect of channel fading on the clipping noise. The clipping noise is added at the transmitter and hence fades with the signal. Here, the authors show that the "bad" subcarriers that dominate the error performance of the OFDM system are least affected by the clipping noise and, as a result, the degradation in the error performance of OFDM system in fading channels is very small.